Identifikace a prevence chyb při montáži klimatizačních sestav - Vyškovský, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Předmětem a cílem této diplomové práce je identifikace a prevence chyb při montáži klimatizačních sestav v automobilovém průmyslu. Diplomová práce byla zpracována ve spolupráci s firmou Halla Visteon Climate Control v Novém Jičíně. V teoretické části jsou detailně rozebrány a popsány přístupy a metody k řešení identifikací chyb a jejich předcházení. Praktická část je zaměřená na identifikaci a prevenci chyb při montáži.

The subject of this master thesis is identification and prevention of mistakes during assembly process of air conditioning system in automobile industry. Thesis was created at Halla Visteon Climate Control Company in the Nový Jičín. The theoretical part is dealing with failure mode and effect analysis and seven quality basic tools for detection of failure and prediction of the failure. The practical part is focused on identification and analysis of failures at the assembly line.
Identification and prevention of errors during the assembly of air-conditioning systems
Keywords: Identifikace; prevence; automobilový průmysl; klimatizace; FMEA; Identification; prevention; automotive industry; air conditioning; FMEA